Collision, Collusion and Coincidence: Pop Art's Fairground Parallel. Issue 3 (1st September 2016) - Trowell, Ian
Abstract : This article looks at parallel methods, motivations and modes of consumption between formative British pop art and British fairground art. I focus on two strands, the emergent critical work of the Independent Group and the school of artists based at the Royal College of Art under the nominal leadership of Peter Blake. I use iconographical and iconological methods to compare the content of the art, and then examine how pop art tried to create both a critical and playful distancing from established rules and practices of the artistic canon. I focus on non-institutional cultural groupings and diffuse production and consumption models.